Transformasi Digital Dalam Implementasi Smart Tourism di Bali - Rahayu, Yunita; Rinunate, Rinunate; Nanda, Sofia (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Bali’s tourism has undergone significant transformation in the digital era, yet it still faces two major challenges, limited accessibility and uneven digitalization. These issues have sparked scholarly interest in examining the extent to which Bali has applied the principles of smart tourism through accessibility and digitalization to create an inclusive and modern tourist destination. This study employs a qualitative method with a literature review approach, analyzing various sources such as academic journals, government reports, and official tourism statistics. The findings reveal that Bali has implemented several smart tourism strategies, including the development of the “We Love Bali” application, digital training for tourism business actors, and the advancement of disability-friendly infrastructure such as wider sidewalks and inclusive transportation. Nevertheless, these implementations remain uneven across different regions of Bali. This article provides both academic and practical contributions to the development of modern tourism by emphasizing the importance of integrating information technology and inclusivity in building smart destinations. The value of this article lies in offering technology-based and public policy solutions to enhance Bali’s tourism competitiveness at the global level, while also reinforcing the principle of social equity within the tourism sector.